Penerapan Algoritma Boyer Moore Untuk Pencarian Data Member Pada PT. Boenk Cosmetic Manufacture Berbasis Desktop - Aulia, Masruri (STMIK Budi Darma, 2020)
PT. Boenk Cosmetic Manufacture is a factory that developed in 2013 in order to deal with globalization, in addition to the large market interest in the products of this factory so as to maintain the factory's existence and consistency, this plant was developed. This company has fulfilled CPKB (How to Make Cosmetics better). PT.Boenk Cosmetic Manufacture every month experiences the addition of new members based on the passage of time members will increase. The problems that are often faced by the employees of PT. Bunk Cosmetic Manufacture increasingly unstructured member data management when searching for member data information that resulted in repeated errors. And every month it is difficult to get fast and precise member data search results so that the work process takes a lot of time. To overcome these problems, it is necessary to develop a system by implementing string matching algorithms to minimize errors in desktop-based member data search. Used in this research is the Boyer Moore algorithm. Boyer Moore's algorithm was first published by Robert S. Boyer, and J. Strother Moore in 1977. By starting character matching from a fixed window shift from left to right. If a match occurs then a comparison of the character of the text and the character of the previous pattern, ie equally reducing the index and pattern of each by one. By using this algorithm the search process will be faster and a lot of information obtained.